Is early age-related macular degeneration related to carotid artery stiffness? The Atherosclerosis Risk in Communities Study. Issue 4 (11th October 2006) - Cheung, Ning; Liao, Duanping; Amirul Islam, F M; Klein, Ronald; Jin Wang, Jie; Yin Wong, Tien
Abstract : Background/Purpose: Atherosclerosis and vascular stiffness have been implicated in the pathogenesis of age-related macular degeneration (AMD). The association of carotid artery stiffness, a measure of arterial elasticity reflecting early atherosclerosis, with early AMD, was examined in this study. Methods: A population-based, cross-sectional study of 9954 middle-aged people (age range 51–72 years). The presence of AMD signs was determined from fundus photographs according to the Wisconsin grading protocol. Carotid arterial stiffness was measured from high-resolution ultrasonic echo tracking of the left common carotid artery, and was defined as an adjusted arterial diameter change (AADCμ). A smaller AADC reflects greater carotid artery stiffness. The associations of pulse pressure and carotid artery intima–media thickness (IMT) with early AMD signs were also analysed. Results: In the study population, 454 (4.6%) had early AMD. The mean (SD) AADC was 403 (127) μ. After adjusting for age, sex, race/centre, education, cigarette smoking, fasting glucose, lipid profile and inflammatory markers, a smaller AADC was found to be not associated with early AMD (odds ratio 0.94; 95% confidence interval, 0.71 to 1.25) or its component lesions. Other measures of arterial stiffness (pulse pressure) and atherosclerosis (carotid IMT) were also not associated with early AMD. Conclusions: Carotid artery stiffness was not associated with signs of early AMD in this middle-aged population. These data provide no evidence of a link between age-related elastoid changes and early atherosclerotic processes in the carotid arteries and early AMD.